The Netherlandish drawings of the 16th century in Teylers Museum - Bleyerveld, Yvonne 1967-; Veldman, Ilja M. 1944- (Primavera Pers, 2016)
The collection of drawings in Teylers Museum has a widely known international reputation. This book is part of a series in which previously books were published on Italian drawings of the 15th and 16th century, and on Dutch drawings dating from 1575-1630 and 1740-1800. This book describes the 257 Netherlandish drawings by artists born before 1581. The most important group consists of no fewer than 125 sheets by Hendrick Goltzius; nowhere else in the world there are so many of his drawings. Other artists represented in the collection are Jacques de Gheyn II (14 drawings), Johannes Stradanus and Abraham Bloemaert, Jacob Matham, David Vinckboons, Lambert Lombard, Mathijs and Paul Bril, Karel van Mander, Roelandt Savery, Maerten de Vos, Dick Crabeth, Frans Floris, Pieter Aertsen, Pieter Cornelisz Kunst, Jan Swart and Pieter Coecke van Aelst, The texts are written by Ilja M. Veldman, Yvonne Bleyerveld, Michiel Plomp and Bert Schepers
Reihe ermittelt. - Includes bibliographical references and index
Keywords: Teylers Museum / Exhibitions; Teylers Museum; Geschichte 1500-1600; Art, Netherlandish / 16th century / Exhibitions; Drawing; Drawing, Netherlandish / 16th century / Exhibitions; Zeichnung; Niederlande; Ausstellungskatalog; Katalog